An Efficient Depth Estimation Technique Using 3-Trait Luminance Profiling - Usman, I. (Engineering, Technology & Applied Science Research, 2019)
This paper presents an efficient depth estimation technique for depth image-based rendering process in the 3-D television system. It uses three depth cues, namely linear perspective, motion information, and texture characteristics, to estimate the depth of an image. In addition, suitable weights are assigned to different components of the image based on their relative perspective position of either the foreground or the background in the scene. Experimental results on publicly available datasets validate the usefulness of the proposed technique for efficient estimation of depth maps.